Estrogen, Progesterone and Epithelial Ovarian Cancer - Ho Shuk-Mei (BMC, 2003)
Abstract Ovarian carcinoma (OCa) continues to be the leading cause of death due to gynecologic malignancies and the vast majority of OCa is derived from the ovarian surface epithelium (OSE) and its cystic derivatives. Epidemiological evidence strongly suggests that steroid hormones, primarily estrogens and progesterone, are implicated in ovarian carcinogenesis. However, it has proved difficult to fully understand their mechanisms of action on the tumorigenic process. New convincing data have indicated that estrogens favor neoplastic transformation of the OSE while progesterone offers protection against OCa development. Specifically, estrogens, particularly those present in ovulatory follicles, are both genotoxic and mitogenic to OSE cells. In contrast, pregnancy-equivalent levels progesterone are highly effective as apoptosis inducers for OSE and OCa cells. In this regard, high-dose progestin may exert an exfoliation effect and rid an aged OSE of pre-malignant cells. A limited number of clinical studies has demonstrated efficacies of antiestrogens, aromatase inhibitors, and progestins alone or in combination with chemotherapeutic drugs in the treatment of OCa. As a result of increased life expectancy in most countries, the number of women taking hormone replacement therapies (HRT) continues to grow. Thus, knowledge of the mechanism of action of steroid hormones on the OSE and OCa is of paramount significance to HRT risk assessment and to the development of novel therapies for the prevention and treatment of OCa.